How soft repulsion enhances the depletion mechanism. Issue 4 (27th November 2014) - Rovigatti, Lorenzo; Gnan, Nicoletta; Parola, Alberto; Zaccarelli, Emanuela
Abstract : Asymmetric soft binary mixtures experience a much enhanced depletion attraction if compared with the Asakura–Oosawa (AO) model. We show that soft mixtures cannot be mapped onto hard systems and hence soft depletion is not a mere extension of the widely used AO potential. Abstract : We investigate binary mixtures of large colloids interacting through soft potentials with small, ideal depletants. We show that softness has a dramatic effect on the resulting colloid–colloid effective potential when the depletant-to-colloid size ratio q is small, with significant consequences on the colloidal phase behaviour. We provide an exact relationship that allows us to obtain the effective pair potential for any type of colloid–depletant interaction in the case of ideal depletants, without having to rely on complicated and expensive full-mixture simulations. We also show that soft repulsion among depletants further enhances the tendency of colloids to aggregate. Our theoretical and numerical results demonstrate that – in the limit of small q – soft mixtures cannot be mapped onto hard systems and hence soft depletion is not a mere extension of the widely used Asakura–Oosawa potential.